The Design of the Solar System Educational Game Using Forward Chaining Based on a Mobile Application - Dram Renaldi; Edy Edy; Vice Hendra (bit-Tech, 2022)
Technological developments especially in software are not in line with developments in the field of education. This is because most of the modules used by teachers are still in the form of printed books. Some subjects require the help of pictures to provide understanding to children. One of them is natural science subjects, especially the solar system. Therefore, this study aims to design a solar system educational game application using multimedia-based forward chaining. The making of this educational game application uses the Unity game engine with the forward chaining method. The solar system educational game application is a game application that combines games with the explanation of the solar system material in it and is implemented on an android smartphone.